STRATEGY AND PARTICIPATION OF COFFEE AGRO-TOURISM DEVELOPMENT IN WAGIR DISTRICT, MALANG REGENCY - Wuwun Risvita; Rita Parmawati; Fadli Mulyadi; Wenny Mamilianti (Faculty of Animal and Agricultural Science, Diponegoro University, 2023)
The coffee commodity and supported by a unique landscape on Mount Kawi's slopes, is an excellent potential for Wagir District to develop into a coffee agrotourism destination. This development cannot be separated from the cooperation needed from the government to the community, especially farmers so that this Coffee Agrotourism can have a welfare and sustainability impact on society and the environment. Also, this study aims to describe the condition of coffee plantations and the level of community participation in their management and to analyze the company's internal and external factors that can formulate appropriate development strategies. Mixed methods were used in this research, and analytical tools such as AHP-SWOT and the Arnstein Participation Ladder Analysis were used. The study results showed that community participation in developing coffee agro-tourism is still relatively low. It is triggered by limited understanding and knowledge regarding the concept of agro-tourism. Recommendations for development strategies are based on the level of participation and conditions in the field, namely by increasing field extension resources to increase farmer institutions' role in creating good coffee agro-tourism. Good farmer institutions are expected to maintain coffee quality and uniformity of coffee quality through farmer groups and improve marketing efficiency.